Producción de biochar a partir de materia orgánica de cáscara de cacao y cascarilla de arroz, para la recuperación de agua contaminada con metales pesados a nivel de laboratorio. - Zavala Lema, Melanie Ibeth (2023)
This research project was carried out in the laboratories of the Faculty of Agricultural Sciences and Natural Resources of the Technical University of Cotopaxi, with the objective of producing biochar from organic matter from cocoa shells and rice husks, in order to obtain a recovery of water contaminated with heavy metals at the laboratory level. Several methods were used to carry out this process, which involved a series of unitary operations such as: drying of the samples through the gravimetric method, production of biochar through a pyrolysis process at 350°C, 400°C and 500°C, application of the analytical march of group I cations for the qualitative detection of Mercury in water, evaluation of the Mercury removal efficiency carried out through a frequency table and finally the quantitative characterization of biochar. Thus, results were obtained such that the average moisture content is 16.01% for cocoa husk and 16.08% for rice husk and on the other hand, the average ash content was 44.34% and 47.53% respectively. In addition, it was identified that cocoa husk biochar at 350°C is the most efficient in the Mercury removal process, considering that its removal efficiency is 100%, with a pH of 9.47, conductivity of 32.7 mS/cm, moisture of 1.55%, ashes of 15.24%P, volatile materials of 42.53%P and a granulometry of 0.5 mm to 20 mm. Consequently, it is concluded that both types of biochar have the capacity to contribute to the removal of mercury from contaminated water, and their removal efficiency will depend on the drying temperature, pyrolysis production and the amount of biomass, since the lower the amount of biochar the removal will be minimal or null, and the higher the amount, the more efficient the removal of mercury will be.